YouTube for Project Based Learning Publications as e-learning Solutions in the Pandemic Period: Literature Review - Tri Padila Rahmasari; Gesty Mika Juwani; Pupe Piliani; Roza Linda (Pancaran Pendidikan, 2020)
Today, in a pandemic situation, the learning system in schools is now being diverted through Distance Learning (PJJ). The challenge that must be resolved by educators are to present a PJJ concept that is in the line with the free learning policy. The success of education today is largely determined by the approach used, especially for chemistry subjects that have high urgency at the SMA/MA level. One approach that is considered suitable to be applied is the heutagogy approach, integrated with using social media in learning. YouTube can be used as publication media in Project-Based Learning (PjBL). The form of research that used is library research and descriptive analysis methods as technique analysis. This application helps increase creativity because it starts with fundamental questions that encourage students' curiosity. This learning concept can still be used as alternative learning that can increase creativity when this pandemic over.